The acrylic's design or the addition of internal orthodontic wire changes the resistance of orthodontic plates? - Matheus Melo Pithon; Érica Luiza Santana Moreira Sousa; Davi Novaes Ladeia Fogaça; William Soares da Silva; Luciano Brito Rodrigues; Raildo Silva Coqueiro
OBJECTIVE: Evaluate resistance of Hawley retainers in three different acrylic configurations in order to evaluate if its format or the addition of internal wire interferes in its resistance. MATERIAL AND METHOD: 45 Hawley retainers were fabricated, divided into three groups (n = 15): Group 1 - acrylic covering the entire hard palate, Group 2 - plate with relief at the deepest region of the palate, leaving it with a "U" conformation and Group 3 - similar to Group 2, with the addition of 0.7mm wire 2cm internally of the acrylic at the region of the palatine ridges. The compressive strength was tested in a universal mechanical testing machine (Stable Microsystems, London, United Kingdom), measuring the applied force until plate rupture occurred. The differences between the formats being compared by the Kruskal-Wallis test. The significance level was set at 5% (α = 0.05). RESULT: Group 1 showed the highest resistance, with a mean of about five times higher than Group 2 and three times higher than Group 3. CONCLUSION: acrylic reduction in dental retainer plates is directly related to the reduction of its compressive strength, the inclusion of orthodontic wire inside the acrylic increases the resistance of the plate, being a good alternative when more comfort is wanted for the patient without loss of the mechanical characteristics of the dental retainers.